Overview of academic production on family farming: a study on the accounting and management approach (Research, Society and Development, 2023)
Family farming has economic and social relevance in the Brazilian context. However, the use of accounting and managerial practices in these enterprises has been unexploit. The application of management techniques in the rural properties aims to facilitate the insertion of the producer in consumer market, as well to contribute to profitability and continuity of the enterprise. The objective of this research was to analyze the academic production on management and accounting as a subsidy for decision-making in rural properties related to Family farming. Through a systematic review of the literature, carried out in the Web of Science database, 52 articles related to management and accounting in Family farming were selected. The investigations revealed a gap in terms of the number of journals and publications. Based on a critical analysis of the selected studies, it was possible to identify six main categories of difficulties reported in relation to decision-making in small rural properties.